Laboratory-based flight performance of the fall armyworm, Spodoptera frugiperda - Shi-shuai GE; Li-mei HE; Wei HE; Ran YAN; Kris A.G. WYCKHUYS; Kong-ming WU (Journal of Integrative Agriculture, 2021)
In late 2018, the fall armyworm (FAW) Spodoptera frugiperda Smith (Lepidoptera: Noctuidae) made its arrival in China and its populations have since proliferated across most of eastern Asia. While S. frugiperda exhibits a considerable dispersal capacity and engages in long-distance migration, there's only scant information on the species' flight capability. Here, we empirically assessed S. frugiperda flight activity under varying climatic conditions using a flight mill. More specifically, under laboratory conditions, FAW exhibited superior flight performance at 20–25°C and 60–90% relative humidity (RH). When quantifying flight performance over five consecutive nights (i.e., 10 h/night), all flight parameters initially increased and then gradually dropped and FAW adults attained a total flight distance, duration and velocity equal to 63.73 km (48.42–94.12 km) (median, quartile range), 24.12 h (20.87–27.73 h) and 2.73 km h−1 (2.13–3.33 km h−1), respectively. Our work constitutes a first comprehensive assessment of S. frugiperda flight performance and provides baseline information for future efforts to forecast spatiotemporal changes in its geographical distribution, movement patterns and invasion trajectories. Such can ultimately permit a timely and targeted deployment of area-wide pest management measures against this newly-invasive pest in China and across eastern Asia.